2021
DOI: 10.1210/clinem/dgab091
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Weight Loss Strategies for Obesity

Abstract: Context Obesity is a chronic disease that is difficult to manage without holistic therapy. The therapeutic armamentarium for obesity primarily consists of four forms of therapy: lifestyle modification (i.e., diet and exercise), cognitive behavioral therapy, pharmacotherapy, and bariatric surgery. Evidence acquisition Evidence was consolidated from randomized controlled trials, observational studies, and meta-analyses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 154 publications
0
49
0
1
Order By: Relevance
“…93 In a review of long-term weight loss strategies, Kheniser et al, suggested in order to mitigate weight regain overtime, a multidisciplinary approach was needed that included a range of modalities to support weight loss maintenance. 23 These included diet (e.g., use of meal replacements), increases in physical activity, and access to antiobesity medications and to behavioral therapies such as CBT. In another meta-analysis that examined the impact of behavioral and lifestyle interventions and pharmacotherapy on weight regain 12 months after weight loss, the authors reported significantly less weight regain of À1.80 and À1.56 kg, respectively, compared with controls or placebo.…”
Section: Duementioning
confidence: 99%
“…93 In a review of long-term weight loss strategies, Kheniser et al, suggested in order to mitigate weight regain overtime, a multidisciplinary approach was needed that included a range of modalities to support weight loss maintenance. 23 These included diet (e.g., use of meal replacements), increases in physical activity, and access to antiobesity medications and to behavioral therapies such as CBT. In another meta-analysis that examined the impact of behavioral and lifestyle interventions and pharmacotherapy on weight regain 12 months after weight loss, the authors reported significantly less weight regain of À1.80 and À1.56 kg, respectively, compared with controls or placebo.…”
Section: Duementioning
confidence: 99%
“…Multi-level, apart from the individual, would include the social and community, physical (environment) and economic levels of interventions 31 , while a multi-pronged approach at the individual level would encompass not just the lifestyle and behavioural modifications but also the possible combination with pharmacologic, and even bariatric surgical procedures based on individualised riskbenefit assessment. 28,32,33 Since obesity is a chronic, often relapsing and progressive disease, weight regain ("relapse") after weight loss is common, in part consequent to the physiologic counterresponse to negative energy balance. Long-term followup for monitoring of weight regains and obesity-related comorbidities is necessary and prudent.…”
Section: Importance Of a Multi-level And Individualised Multi-pronged Approach To Treat Obesitymentioning
confidence: 99%
“…28,32 Management strategies for weight maintenance/weight regain prevention of at least 6-12 months should be considered during weight loss treatment, understanding that there is also reduced adherence to lifestyle changes with time. 30,33 Some of these measures may involve keeping frequent contact with the patient even after weight loss is attained (e.g. once a month), long-term use of anti-obesity medications, initiation of anti-obesity medications after weight plateau with lifestyle changes and/or intermittent use of very-low or low-calorie diets.…”
Section: Importance Of a Multi-level And Individualised Multi-pronged Approach To Treat Obesitymentioning
confidence: 99%
“…As a complex chronic disease, the management of obesity requires a holistic approach. Although pharmacotherapy and bariatric surgery are indicated with severe obesity, diet, exercise, and cognitive behavioural therapy are the primary strategies for the lifelong management of obesity [ 5 , 28 , 29 ]. Kheniser et al [ 29 ] stated that two years of lifestyle interventions can facilitate a 5% weight loss and that, although a weight regain occurs, both diet and exercise interventions have substantial effects on obesity-associated comorbidities [ 5 , 29 ] and adipose tissue remodelling [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although pharmacotherapy and bariatric surgery are indicated with severe obesity, diet, exercise, and cognitive behavioural therapy are the primary strategies for the lifelong management of obesity [ 5 , 28 , 29 ]. Kheniser et al [ 29 ] stated that two years of lifestyle interventions can facilitate a 5% weight loss and that, although a weight regain occurs, both diet and exercise interventions have substantial effects on obesity-associated comorbidities [ 5 , 29 ] and adipose tissue remodelling [ 30 ]. Moreover, both regular aerobic exercise and the consumption of a hypocaloric diet are associated with a substantial reduction in VAT and liver fat independent of age, biological sex, or ethnicity [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%